2003
DOI: 10.1073/pnas.0437992100
|View full text |Cite
|
Sign up to set email alerts
|

Nanodissection and high-resolution imaging of the Rhodopseudomonas viridis photosynthetic core complex in native membranes by AFM

Abstract: In photosynthesis, highly organized multiprotein assemblies convert sunlight into biochemical energy with high efficiency. A challenge in structural biology is to analyze such supramolecular complexes in native membranes. Atomic force microscopy (AFM) with high lateral resolution, high signal-to-noise ratio, and the possibility to nanodissect biological samples is a unique tool to investigate multiprotein complexes at molecular resolution in situ.Here we present high-resolution AFM of the photosynthetic core c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
194
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(211 citation statements)
references
References 32 publications
(35 reference statements)
14
194
1
Order By: Relevance
“…Subsequently, a similar ellipticity was observed in AFM topographs of the membrane-bound Rps. viridis RC-LH1 complex, only to alter to a circular shape upon removal of the RC (16). Our topographs of the R. rubrum complex differ, in that ellipses are observed whether or not the RC is present.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Subsequently, a similar ellipticity was observed in AFM topographs of the membrane-bound Rps. viridis RC-LH1 complex, only to alter to a circular shape upon removal of the RC (16). Our topographs of the R. rubrum complex differ, in that ellipses are observed whether or not the RC is present.…”
Section: Discussionmentioning
confidence: 69%
“…2f, but qualitatively speaking, it means that the LH1 complex forms a slightly raised rim around the RC. Our measurements can be compared with those of Scheuring et al (16), who examined the periplasmic side of membranes from Rps. viridis, and found that the LH1 complex protruded from the membrane by ϳ10 Å.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations